Relationship between antioxidant capacity and angiotensin-converting enzyme inhibitory activity of papain-generated protein hydrolysates and peptides from palm kernel cake proteins - Zarei, Mohammad; Abdul Hamid, Azizah; Hasan, Belal J. Muhialdin Mula; Saari, Nazamid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Palm kernel cake (PKC) proteins were hydrolysed in the presence of seven proteolytic enzymes. The antioxidant and antihypertensive activities of each protein hydrolysate were evaluated. Papain-generated protein hydrolysate showed the highest antioxidant effects measured by radical scavenging activity (65%), iron (Fe)(II)-chelating activity (65%), and antihypertensive activity (71%). The results revealed a strong correlation between the antioxidant activity of the protein hydrolysates with angiotensin-converting enzyme (ACE) inhibitory activity (R2 = 0.69 - 0.98), except for trypsin-generated hydrolysate (R2= 0.22). The most potent protein hydrolysate was fractionated and profiled using reversed-phase high-performance liquid chromatography and isoelectric focusing; peptides were subsequently isolated and identified by tandem mass spectrometry. The individual peptides were evaluated for antihypertension potential. A positive correlation was identified between radical scavenging activity and Fe(II)-chelating activity together and ACE inhibitory activity with R2 = 0.69 - 0.98. The findings indicate that there was a positive relationship between the antioxidant and antihypertensive activities of protein hydrolysates and bioactive peptides from PKC proteins.